The Future Of The Auditing Profession In The Era Of Digital Transformation Technologies - Besseri, Rima; Saidi, Fares (جامعة الوادي University of Eloued, 2025)
This study emphasizes the significance of blockchain technology as one of the leading modern digital technologies that contribute to the development and enhancement of the auditing profession. To thoroughly address the topic, a descriptive-analytical method was employed to answer the main research question with the utmost precision. This approach was used to obtain scientific results and analyze them objectively. The findings reveal that blockchain is highly effective in reducing time and costs while improving efficiency and accuracy. Furthermore, the technology enhances transparency and credibility through immutable records and offers innovative solutions that accelerate auditing processes, securely and systematically store data, and facilitate efficient analysis.
The Future of the Auditing Profession in the Era of Digital Transformation Technologies - Blockchain Technology as a Model
مقال
Keywords: Digital transformation; Auditing profession; Technology; Financial information reliability; Blockchain.